EFEKTIFITAS PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PT. GOODYEAR INDONESIA DI KOTA BOGOR - Syaiful aditya saputra; Endeh Suhartini; Mulyadi Mulyadi (JURNAL HUKUM DE'RECHTSSTAAT, 2020)
A common issue is that often employees do not use personal protective equipment is complete. Many factors cause this to happen, could be due to the limitations of the tools provided by the agency's own employees or for disobedience. Lack of awareness of workers to always use PPE can inhibit the production process. It also happens to PT Goodyear Indonesia Tbk, where workers are still considers PPE only a mere rule without thinking that the benefits brought about much greater than just the rules that must be adhered to, so there are many violations that occur in its application. In this study, the method used is a method socio-juridical (empirical), namely the law as a symptom of society, as a social institution or patterned behavior.From observations in the field, there are still some workers not wearing PPE is complete when entering the workplace or working in a workplace that has the potential and factors specific harm, although the company has set the obligation to use personal protective equipment for all workers.